2020
DOI: 10.1177/1179554920953091
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Integrated Positron Emission Tomography/Computed Tomography (PET/CT) and Bone Marrow Examination in Staging Large B-Cell Lymphoma

Abstract: Introduction: In the era of routine use of positron emission tomography/computed tomography (PET/CT) for staging, it is not yet clear whether PET/CT can replace bone marrow biopsy for the assessment of bone marrow involvement in large B-cell lymphoma. Objectives: To compare the clinical utility of bone marrow biopsy and PET/CT scanning in the staging of large B-cell lymphoma. Methods: This was a retrospective analysis of all patients who presented to single center over a 4-year period with large B-cell lymphom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…This systematic review involved some limitations. In some studies PET/CT images were interpreted using qualitative criteria [15][16][17]19,20,22,26,29,31,[34][35][36][37][38][39]42,43,47,48,50,[52][53][54], whereas in other studies both qualitative and quantitative criteria were used [18,21,[23][24][25]27,28,30,32,33,40,41,[44][45][46]49,51,55]. As the qualitative evaluation is based on a subject's experience, this might underestimate the PET/CT diagnostic performance.…”
Section: Discussionmentioning
confidence: 99%
“…This systematic review involved some limitations. In some studies PET/CT images were interpreted using qualitative criteria [15][16][17]19,20,22,26,29,31,[34][35][36][37][38][39]42,43,47,48,50,[52][53][54], whereas in other studies both qualitative and quantitative criteria were used [18,21,[23][24][25]27,28,30,32,33,40,41,[44][45][46]49,51,55]. As the qualitative evaluation is based on a subject's experience, this might underestimate the PET/CT diagnostic performance.…”
Section: Discussionmentioning
confidence: 99%
“…Repeat PET-CT after treatment to assess if uptake resolves with the resolution of involved nodal sites ( 18 ).…”
Section: Methods For Bone Marrow Involvement Detectionmentioning
confidence: 99%
“…Al-Sabbagh et al. found that none of the patients displaying diffuse bone marrow changes on PET-CT had a positive bone marrow biopsy, and conversely, none of the patients with a positive bone marrow biopsy exhibited diffuse bone marrow uptake on PET without a focal lesion ( 18 ). In contrast, another study reported that diffuse bone marrow uptake on PET-CT scans, conducted for patients with aggressive NHL, was frequently associated with a positive bone marrow biopsy ( 56 ).…”
Section: Patterns Of Bone Marrow Involvement In Dlbclmentioning
confidence: 99%
See 2 more Smart Citations